The Effect of Covid 19 on Bitung Micro Business Performance - Chrisanty Victoria Layman (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Microbusinesses under Dinas Koperasi Usaha Kecil Menengah Bitung faced plenty of struggles to make ends meet given the uncertainty of the Covid19 pandemic. The micro-business owners have to adapt and adjust their businesses for survivability.Objectives: This study aims to analyze the effect of Covid19 and market competition on these micro and small enterprises in Bitung, Indonesia which survived and still has business performance, either financial or non-financial. In addition, this study seeks to analyze the effect of Covid19 on the adoption of digital marketing that might influence business performance.Methodology: The study uses data from 38 micro-business in Bitung that are currently active and has been surviving through the Covid19 pandemic. Data analysis and hypothesis testing are done using Partial Least Squared Modelling (PLS-SEM) using SMART PLS.Finding: Results of this study shows that competition intensity has a positive influence on the adoption of digital marketing. In addition, digital marketing adoption positively influences both financial and non-financial performances.Conclusion: Contrary to common belief, it is competition intensity rather than the perception of Covid19 that has contributed to the adoption of digital marketing which in turn contributed to the business financial performance of micro businesses in Bitung.